Optimasi Parameter pada Mesin 3D Printer terhadap Kekuatan Tarik dan Kekasaran Permukaan Produk Menggunakan Metode Taguchi Grey Relational Analysis - Mega Tri Yoningtias; Farizi Rachman; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
The world of the manufacturing industry continues to develop and one of the technologies that support the manufacturing industry in the era of the industrial revolution 4.0 is 3D printingtechnology. It is very important to know the mechanical properties of 3D printing materials, one of which is tensile strength. Low tensile strength causes the product to experience mechanical failure such as yielding and fracture. High surface roughness causes the wear of components and affects their functional factors. To get a product of good quality so that the resulting product has high tensile strength and low surface roughness, research is needed to find the right and optimal combination of process parameters in the 3D printing process. Tensile strength and surface roughness will be observed. The material used is ABS filament. Layer height, infill pattern, and nozzle temperature are varied. Design of Experiment using the Taguchi method in the form of an orthogonal matrix L9(34) with three replications and using Grey Relational Analysis. From the results of the study, it was found that the most optimal combination of independent variables for the response variables of tensile strength and surface roughness simultaneously was layer height at level 1 with a value of 0.1 mm, infill patternat level 2 with line pattern and nozzle temperature at level 1 with a value of 230°C. The layer height parameter gives a contribution percentage of 49.55%, infill pattern 46.92%, and nozzle temperature 1.67%.